A Synthesis Paper: How a Destination Capturing Value from the Its Visitors ? - Diin Fitri, SE., MM. (Journal of Management and Leadership, 2019)
As well in other business, the destination should able to improve their strategy in order to becompetitive in the market. This paper aims to deliver a synthesis papers that shows on how adestination able do its marketing strategy to capture value for its visitors based on the work doneby Yang & Tan, (2017) Li, et al., (2017), Mariani, et al., (2015). It is found that visitors havedifferent needs and wants, and the destination able to doing STP by first understand the motivationfor the tourist to, In doing integrated marketing program, the destination should able to provideinnovative events and to incorporated the destination products/service to capture more than onesegments. For promotion, supplying information to the visitors also important for promotion. Theorganization able to use the social media to maintain the relationship with the customers, thedestination will be able to gain some value from the customers as it able to enhance corporateimage, customers loyalty and corporate revenue.